Highly stable lithium anodes from recycled hemp textile. Issue 12 (19th January 2022) - Wang, Zhiyu; Zhang, Peng; Chen, Shasha; Usman, Ken Aldren S.; Hegh, Dylan; Kerr, Robert; Zhang, Hongjie; Qin, Si; Zhang, Chuyang; Liu, Dan; Wang, Xungai; Lei, Weiwei; et al.
Abstract : A cost-effective and scalable approach to produce highly stable Li composite anode from hemp textile waste with long cycling life. Abstract : Three-dimensional lithium (Li) hosts have been shown to suppress the growth of Li dendrites for next generation Li metal batteries. Here, we report a cost-effective and scalable approach to produce highly stable Li composite anodes from industrial hemp textile waste. The hemp@Li composite anodes demonstrate stable cycling both in half and full cells.